Functions, mechanisms, and therapeutic implications of noncoding RNA in acute myeloid leukemia - Xiaokang Wang; Yong Tong; Tianrong Xun; Haixing Feng; Yuhe Lei; Yuanqing Li; Kit Hang Wu; Fang Qiu (Fundamental Research)
Acute myeloid leukaemia (AML) is a malignant disease of myeloid hematopoietic stem/progenitor cells. Despite improved understanding of the pathogenesis of AML since the 1980s, the standard treatment for AML has remained virtually unchanged. Numerous studies have found poor survival rates and high relapse rates among older patients with AML. Several novel therapies for AML, including cytotoxic drugs, genetically- and epigenetically-targeted drugs, and immunotherapies, have been developed in recent years. Alternative treatments with improved efficacy are required for AML because many patients cannot tolerate the toxic effects of chemotherapy. Non-coding RNAs, including microRNAs (miRNAs), long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs), are attractive treatment targets for cancers and several other diseases. LncRNAs, miRNAs and circRNAs regulate DNA transcription and translation. Over the past decade, significant efforts have been made to develop RNA-based therapies, mainly antisense oligonucleotides and small interfering RNA, some of which have been approved for clinical use. Here we reviewed the mechanisms underlying the in vitro and in vivo effects of promising targets and potential drugs, focusing on the drugs most likely to be used for clinical treatment, to aid in the development of precision therapy for AML.